Services Application Program In Population Administration of District Cipadu Using Microsoft Access 2002 - Dyah Murthiwi (Jurnal Sistem Informasi, 2005)
Human dependence of information to meet the increasing these factors, the required tools for high-speed and highly accurate in processing these data. Computers are the tools of data processing that can be relied upon to perform data processing in large numbers. Cipadu of District located at Jl. Pearls No.1 Cipadu is the office of District that specializes in services for population. The relationship of government agencies so as to always be able to provide the best services, quickly and accurately to the public. But because the processing of residence services are less organized and not integrated, as a result of completing the service activity was slow and less accurate. It required an application program that can help to make treatment services in Kelurahan Cipadu population, which is expected to program services can be better and the reporting of any activity can be more accurate and efficient. Also expected by the community service application program can facilitate this in the village pengoprasiannya and minimize errors in the data pengimputan possible. This application programming using Microsoft Access 2002, which is easy in use. Mengguanakan addition to Microsoft Access 2002 can pass the data to edit, modify and display a back-up data at any time, and with this application program is expected to assist the implementation of population service activities to become more effective and efficient and obtain a satisfactory outcome and better .